Plasmonic effects arising from a grooved surface of a gold nanorod. (24th February 2017) - Chau, Yuan-Fong Chou; Lee, Chuanyo; Huang, Hung Ji; Lin, Chun-Ting; Chiang, Hai Pang; Mahadi, Abdul Hanif; Voo, Nyuk Yoong; Lim, Chee Ming
Abstract: A single gold nanorod (GND) with a grooved surface is a unique structure which is composed of an array of grating notches or an array of air-holes on the surface of the metal nanorod (MND). In this paper, surface plasmon resonance (SPR) effects arising from the different patterns of GNDs with a grooved surface have been investigated by using finite element method and compared to the smooth surface of the same counterparts. Scattering cross section spectra of symmetric and asymmetric grooves on the surface of GNDs are studied to demonstrate that the proposed structures with a grooved surface can support the SPRs with enhanced both localization and propagation field intensities corresponding to their peak resonance wavelengths and polarization directions. The obtained longitudinal modes are beneficial for signal harvest, while the transverse modes are beneficial for signal emitting. These SPR effects can be useful for correlating specific plasmonic applications in the nanophotonic field with geometrical features on the nanometer scale and, therefore, provide a better understanding of the mechanism of the photoluminescence images on MNDs with/without a grooved surface.